Spectrally entangled biphoton state of cascade emissions from a Doppler-broadened atomic ensemble. (13th June 2019) - Chang, T H; Lin, G-D; Jen, H H
Abstract: We theoretically investigate the spectral property of biphoton state from the cascade emissions from a Doppler-broadened atomic ensemble. This biphoton state is spontaneously created in the four-wave-mixing process. The upper transition of the emissions lies in telecom bandwidth, which prevails in fiber-based quantum communication for low-loss transmission. We obtain the spectral function of the biphoton state in terms of superradiant decay rates of the lower transition, excitation pulse durations, and temperature of the medium. We quantify their frequency entanglement by Schmidt decomposition and find that more entangled source can be generated with longer excitation pulses, enhanced decay rates, and significant Doppler broadening. A minimally entangled biphoton source can also be located at some optimal temperature of the atoms. By tuning these parameters, this biphoton source allows spectral shaping of continuous frequency entanglement, which is useful in multimode long-distance quantum communication.